Co-existence of overweight/obesity and stunting: it's prevalence and associated factors among under - five children in Addis Ababa, Ethiopia - Alem Sebsbie; Abebe Minda; Sindew Ahmed (BMC, 2022)
Abstract Background Double burden of malnutrition is a global problem posing a serious public health challenge especially in low- and middle-income countries including Ethiopia, where a high prevalence of under-nutrition continues to exist and overweight is increasing at an alarming rate. Although both under-nutrition and over-nutrition are investigated extensively in Ethiopia, evidence about the double burden of malnutrition especially at the individual level is very limited. Objective To assess the prevalence of the co-existence of overweight/obesity and stunting and associated factors among under-five children in Addis Ababa, Ethiopia at an individual level. Methods Institution-based cross-sectional study was conducted from May to June 2021 among 422 mothers to child pairs in Addis Ababa. Twenty-nine (30%) of the health centers in Addis Ababa were selected to take part in the study using a simple random sampling technique. The total sample size was allocated proportionally to each of the selected health centers based on their performances within 6 months prior to the study. A systematic random sampling method was used to select the study participants. An interviewer-administered structured questionnaire was used to collect data. Descriptive statistics and a hierarchical logistic regression model were used to characterize the study population and to identify factors that are associated with the outcome variable respectively. Odds ratio along with 95% CI were estimated to measure the strength of the association. The level of statistical significance was declared at a p-value less than 0.05. Results The prevalence of the co-existence of overweight/obesity and stunting was 5.1% with 95% CI (2.9-7.1%). The hierarchical logistic regression analysis revealed that child age (6-23 months) [(AOR = 2.86, 95% CI: (1.02-8.04)], maternal education status (non-educated) [(AOR = 4.98, 95% CI: (1.33-18.66)], maternal age during birth (≥ 28 years) [(AOR = 0.22, 95% CI: (0.06-0.79)] and childbirth order (3+) [(AOR = 6.38, 95% CI: (1.03-39.7)] were significantly associated with the co-existence of overweight /obesity and stunting. Conclusion and recommendations: The study revealed that the prevalence of the co-existence of overweight/obesity and stunting is low in Ethiopia. However, local and national nutrition policies and programs should be tailored and implemented to simultaneously address both under-nutrition and over-nutrition.